The Current Factors of Ensuring the Activities of Public Administration Regarding the System of Social Adaptation of Children with Disabilities - Kondratenko, Vitalii; Manzhula, Andrii; Sobol, Yevhen (Journal of History Culture and Art Research, 2020)
The article is devoted to the issues of organization and provision of proper level of social rehabilitation by state authorities and local self-government bodies in order to overcome maladaptation in children with disabilities. It has been substantiated that social adaptation is an active parity relationship between society and a person, aimed at finding out by society the possible conditions for adapting to the social life of the individual; bringing behavior of a person in accordance with generally accepted norms and values; ensuring economically stable and safe existence in an adapted environment; social integration of heterogeneous elements of society. Rehabilitation of people with disabilities considers one of the main areas of activity of public administration in the field of providing subjective rights. The principles of activity of rehabilitation institutions have been described, individual, process-technological and state-regional levels of rehabilitation have been specified. The argumentation has been given concerning positive adaptive influence on the personality through the implementation of inclusive education, which is a flexible system of education with medical and social and psychological and pedagogical support. As a result of the analysis of official statistics, the conclusion has been reached regarding the low level of social rehabilitation of children with disabilities, which leads to a negative dynamics in the development of their disadaptation.